1997
DOI: 10.1210/endo.138.3.4999
|View full text |Cite
|
Sign up to set email alerts
|

Activation of G Proteins Mediates Flow-Induced Prostaglandin E2Production in Osteoblasts

Abstract: Interstitial fluid flow may play a role in load-induced bone remodeling. Previously, we have shown that fluid flow stimulates osteoblast production of cAMP inositol trisphosphate (IP3), and PGE2. Flow-induced increases in cAMP and IP3 were shown to be a result of PG production. Thus, PGE2 production appears to be an important component in fluid flow induced signal transduction. In the present study, we investigated the mechanism of flow-induced PGE2 synthesis. Flow-induced a 20-fold increase in PGE2 production… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0
1

Year Published

1998
1998
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(10 citation statements)
references
References 34 publications
0
9
0
1
Order By: Relevance
“…Previous studies have demonstrated that G proteins were involved in strain‐activated proliferation of human endothelial cells [18]. These molecules mediated steady/transient fluid shear stress‐stimulated nitric oxide production [19,20], and flow‐induced prostaglandin E 2 production by osteoblasts [21]. Extracellular signal‐regulated kinase (ERK), a member of the mitogen‐activated protein kinase family, mediated the transduction of mechanical stimulation into intracellular signals that regulate cell proliferation and differentiation [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that G proteins were involved in strain‐activated proliferation of human endothelial cells [18]. These molecules mediated steady/transient fluid shear stress‐stimulated nitric oxide production [19,20], and flow‐induced prostaglandin E 2 production by osteoblasts [21]. Extracellular signal‐regulated kinase (ERK), a member of the mitogen‐activated protein kinase family, mediated the transduction of mechanical stimulation into intracellular signals that regulate cell proliferation and differentiation [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…The in vitro mechanical stimulation of bone cells by fluid flow has been reported to impact the levels of many biochemical factors including intracellular calcium (5,6), nitric oxide (4,(7)(8)(9), prostaglandin E 2 (3,4,7,8), the expression of the genes for osteopontin, cyclooxygenase-2, and c-Fos (6,(10)(11)(12) as well as other intracellular messengers and transcription factors (6,(13)(14)(15). This mechanostimulation of bone cells in vitro by fluid flow mimics the physiological response of bone cells in vivo where pressure gradients from mechanical loading of locomotion and other stressors deform the mineralized bone matrix and move extracellular fluid radially outward toward the cortex through the lacunocanalicular network (16)(17)(18)(19).…”
mentioning
confidence: 99%
“…Fluid flow-induced shear stress applied to osteoblastic cells for several hours has been shown to stimulate the release of nitric oxide (5,8,9), a short-lived radical and messenger implicated in several cellular functions, and prostaglandin (4,5,8,10,11) that may have an autocrine effect on osteoblastic cells. Fluid shear has been shown to up-regulate a variety of genes, including those of osteopontin and cyclooxygenase-2, and several other transcription factors and intracellular messenger systems like cAMP, mitogen-activated protein kinase, and G proteins (12)(13)(14)(15)(16)(17). In addition, short-term fluid flow causes changes in the cell cytoskeleton by altering structural proteins and gap junctions (18)(19)(20).…”
mentioning
confidence: 99%